Ethernet OAM key enabler for carrier class metro ethernet services. - McFarland, Mike (IEEE Communications magazine)
The onset of Ethernet as a metropolitan and wide area networking, technology has driven the need for a new set of operations, administration, and maintenance protocols. Service provider networks are large and complex with a wide user base, and they often involve different operators that must work together in order to provide end-to-end services to enterprise customers. With enterprise end customer demands ever increasing, so have the requirements on service provider Ethernet networks increased, particularly in the areas of availability and mean time to repair. Ethernet OAM addresses these areas and more, and is a tool that translates directly to the competitiveness of the service provider. Ethernet OAM is a broad topic, but this article focuses on three main areas that are most in need by service providers and are rapidly evolving in the standards bodies: Service OAM, Link OAM and Ethernet LMI. These OAM protocols have unique objectives but are complementary to each other. Service OAM provides monitoring and troubleshooting of end-to-end Ethernet service instances, while link OAM allows a provider to monitor and troubleshoot an individual Ethernet link. There are of course many different ways to provide this type of functionality, but fortunately standards bodies such as ITU Study Group 13, IEEE 802.3 Clause 57 (formerly 802.3ah), IEEE 802.1ag Connectivity Fault Management, and the Metro Ethernet Forum are all driving toward consistent recommendations and standards for Ethernet OAM.